Hydroxychloroquine safety outcome within approved therapeutic protocol for COVID-19 outpatients in Saudi Arabia (2020)
Background: Global healthcare is challenged following the COVID-19 pandemic, since late 2019. Multiple approaches have been performed to relieve the pressure and support existing healthcare. The Saudi Arabian Ministry of Health (MOH) launched an initiative to support the National Healthcare System. Since the 5th of June 2020, 238 outpatient fever clinics were established nationwide. This study aimed to assess the safety outcome and reported adverse events from hydroxychloroquine use among suspected COVID-19 patients. Method: A cross-sectional study included 2,733 patients subjected to MOH treatment protocol (hydroxychloroquine) and followed-up within 3-7 days after initiation. Data was collected through an electronic link and cross-checked with the national database (Health Electronic Surveillance Network, HESN) and reports from the MOH Morbidity and Mortality (M&M) Committee. Results: 240 patients (8.8%) discontinued treatment because of side effects (4.1%) and for non-clinical reasons in the remaining (4.7%). Adverse effects were reported among (6.7%) of all studied participants, including mainly cardiovascular (2.5%, 0.15% with QTc prolongation), and gastrointestinal (2.4%). No Intensive Care Unit admission or death were reported among these patients. Conclusion: Our results show that hydroxychloroquine for COVID-19 patients in mild to moderate cases in an outpatient setting, within the protocol recommendation and inclusion/exclusion criteria, is safe, highly tolerable, and with minimum side effects.